2019
DOI: 10.1002/jbm.b.34489
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐by‐layer films based on catechol‐modified polysaccharides produced by dip‐ and spin‐coating onto different substrates

Abstract: Layer‐by‐layer films based on chitosan and hyaluronic acid were produced by dip‐ and spin‐coating techniques onto glass, 316L stainless steel and titanium. These natural polymers were modified with catechol groups, in order to build coatings with improved adhesive properties. Polymeric coatings were exclusively composed by both modified polymers whereas the multifunctional coatings combined an inorganic phase of bioactive glass nanoparticles with the polymeric layers to confer bioactivity. Ultraviolet–visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
(99 reference statements)
1
13
0
Order By: Relevance
“…[ 17 ] The stability of these coatings has been further enhanced with catechols. [ 18 ] Their introduction also made it possible to incorporate copper particles through a coordination bond. In this way, coatings were obtained to gradually release heparin and nitrogen oxide (NO).…”
Section: Layer‐by‐layer Approachmentioning
confidence: 99%
“…[ 17 ] The stability of these coatings has been further enhanced with catechols. [ 18 ] Their introduction also made it possible to incorporate copper particles through a coordination bond. In this way, coatings were obtained to gradually release heparin and nitrogen oxide (NO).…”
Section: Layer‐by‐layer Approachmentioning
confidence: 99%
“…PE gels that are classified as natural are typically based on materials obtained from the natural world. The natural biopolymers that are commonly observed as major constituents in PE gels include polymers such as CHT, HA and heparin (HEP) [ 22 , 23 ]. These glycosaminoglycans (GAGs) are naturally found in the ECM at various locations, particularly the connective, neural and epithelium tissue.…”
Section: Fundamentals Of Pe Gelsmentioning
confidence: 99%
“…As two adhesive charges were present, C-HA was chosen as the ending layer due to C-CHT being selected as the stable precursor layer for the deposition of the assembly. The study further demonstrated how a higher content of catechol groups improves the wetting contact angle that aids in a stronger bond formation in wet environments, showing potential for tissue engineering [ 22 ].…”
Section: Fabrication Of Different Types Of Pe Gelsmentioning
confidence: 99%
See 2 more Smart Citations